Studi Entrepreneurship dalam Pandangan Hadis - Siti Rahmah; Wahyudin Darmalaksana (Gunung Djati Conference Series, 2022)
This study aims to discuss the hadith about entrepreneurship. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about entrepreneurship in the history of Ahmad No. 2817. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Ahmad No. 2817 is relevant to be used as motivation, creativity, innovation, and development in the field of entrepreneurship.